ESD Implementation at the Dawn of the UN-DESD: An International Comparative Study of School Subjects - Bagoly-Simó, Péter (Journal of Geography Education, 2014)
The Decade of Education for Sustainable Development proclaimed by the United Nations for the years 2005-2014 aims at a strong implementation of Education for Sustainable Development (ESD) into all forms of education. Despite a range of measures taken and programs developed, topics that discuss contemporary and future challenges of humanity have received marginal attention as yet. Therefore, this paper takes a closer look at the implementation of ESD topics into subject curricula of formal education. When doing so, it analyzes the contribution of the topics to both subject-specific skill acquisition and ESD. Mixed methods served to map the implementation of 46 topics in Bavarian (Germany), Romanian, and Mexican national curricula for lower secondary education. The results show different patterns of implementation that produce specialization and segmentation. Moreover, none of the three curricula displays a broad and deep implementation of ESD-topics. While Geography is in all three case studies the leading subject implementing ESD topics, Biology, Physics, Chemistry, technical subjects, and Ethics specialize on few topics and often discuss them broadly.